2016
DOI: 10.1167/iovs.16-20279
|View full text |Cite
|
Sign up to set email alerts
|

TRPV2 Channels Contribute to Stretch-Activated Cation Currents and Myogenic Constriction in Retinal Arterioles

Abstract: Our results suggest that retinal VSMCs express a range of mechanosensitive TRP channels, but only TRPV2 appears to contribute to myogenic signaling in this vascular bed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 59 publications
1
45
0
Order By: Relevance
“…Some of the S3 profiles with more pronounced rigidity are members of the TRPV, Hv1, and KCNQ families, as well as domains DIII and DIV of Na V 1 channels (Figure 1). In accordance with our prediction on S3 rigidity facilitating mechanosensitivity, KCNQ channels, TRPV2 and Hv1 have recently been recognized as directly activated by the membrane stretching [95][96][97][98]. In Hv1 proton channels, for which the whole VSD is the more rigid in the VGIC superfamily (see Figure 1, top panel), the effect of negative pressure of -10 mmHg in the pipette clearly shifts the activation curve ∼14.5 mV [98].…”
Section: Voltage Dependence and Mechanosensitivitysupporting
confidence: 85%
“…Some of the S3 profiles with more pronounced rigidity are members of the TRPV, Hv1, and KCNQ families, as well as domains DIII and DIV of Na V 1 channels (Figure 1). In accordance with our prediction on S3 rigidity facilitating mechanosensitivity, KCNQ channels, TRPV2 and Hv1 have recently been recognized as directly activated by the membrane stretching [95][96][97][98]. In Hv1 proton channels, for which the whole VSD is the more rigid in the VGIC superfamily (see Figure 1, top panel), the effect of negative pressure of -10 mmHg in the pipette clearly shifts the activation curve ∼14.5 mV [98].…”
Section: Voltage Dependence and Mechanosensitivitysupporting
confidence: 85%
“…Such actions of SKF96365 were similar to those of LY364947. Other TRP inhibitors and activators at concentrations that have been reported to be effective, such as the TRPV1-3 activator 2-APB (100 mM) [33,34], TRPV1 activator capsaicin (100 nM) [35], TRPV4 activator GSK1016790A (25 nM) [36,37], TRPV1 inhibitor AMG9810 (10 mM) [32], and TRPV4 inhibitors RN1734 (10 mM) [38] and HC067047 (1 mM) [36,39], exhibited smaller actions. A cell viability assay revealed that these compounds did not significantly alter the viability index of dermal fibroblasts to account for their action on gel contraction (Suppl.…”
Section: Involvement Of Trpv Channels In the Contraction Of Collagen Gelmentioning
confidence: 99%
“…Tranilast has been used clinically for the prevention of hypertrophic scar formation [27]. This compound was reported to inhibit TRPV2 channels [24,39]. Here, we tested the effects of SKF96365 and tranilast on fibroblast differentiation and contraction of the KC(+) model.…”
Section: Inhibition Of Gel Contraction A-sma Production and Tgf-b1 mentioning
confidence: 99%
See 1 more Smart Citation
“…Other TRP channels such as TRPV2 have been proposed to play an important role in the stretch-activated cation currents and myogenic constriction in retinal arterioles [163].…”
Section: Other Sensory Trp Channelsmentioning
confidence: 99%